Method for Calculating Heat Transfer in a Heat Accumulator Using a Phase Change Material with Intensification Due to Longitudinal Fins - Vladimir Lebedev; Andrey Deev; Konstantin Deev (Energies)
One of the challenges in energy supply for isolated power systems is maintaining a steady balance between generated and consumed energy. The application of energy storage systems and flexible energy sources is the most preferable approach for these systems. Small- and medium-sized nuclear power plants are promising, carbon-free options for energy supply to isolated power systems. However, these plants have low maneuverability. To solve this problem, this article discusses the use of a thermal accumulator using a phase change material (solar salt) to heat feedwater. Tubes with longitudinal fins are used to intensify heat transfer in the storage system. This paper presents a method for calculating heat transfer along the entire heat exchange surface of such an accumulator. A series of 2D simulations were conducted to study the solidification process of solar salt around a heat exchange tube at various temperatures on the inner wall surface. The regression dependences of heat transfer on the temperature of the inner surface of the wall and the thickness of the solid PCM layer were determined. Using the presented method and the obtained regression dependencies, we determined the time graphs of the temperature change in the heat transfer fluid at the outlet of the accumulator during discharge. Based on the results presented, it was found that an accumulator with 72.7 tons of solar salt (dimensions: 6 × 3.71 × 2.15 m) can replace a high-pressure heater №1 at a low-power nuclear power plant (50 MW) during 3450 s.